Formation of granulomas in liver of silica-treated rats. - Kanta, J. (1986)
Hepatic silicosis was induced in rats by an intravenous injection of saline-suspended silica, 40 mg/kg of body weight. Changes in the liver were examined by biochemical, histological and histochemical methods. Infiltration of the liver parenchyma by polymorphonuclear leucocytes was observed only on the first day after silica treatment. Formation of silicotic nodules began on the first day by clustering of liver macrophages. A 22% increase in liver weight and a 67% increase in total liver DNA reflected accumulation of cells in the liver by day 28 after silica injection. Local cell division contributed to this increase. Almost all cells in the nodules contained carbon when the rats had been given ink before silica. Macrophages showed high activity of lysosomal esterases on the first few days after silica treatment; the activity disappeared later. Large granulomas containing hundreds of cells including lymphocytes were seen 226 days after treatment. Hydroxyproline content per gram of liver tissue increased by 35% and 58% by day 80 and 162, respectively. Connective tissue formed capsules around the nodules and grew to their inside. Activities of lysosomal enzymes, beta-D-galactosidase and acid proteases, in serum were increased by 20% and 300%, respectively, 35 days after treatment. Neither malondialdehyde concentration nor superoxide dismutase activity was elevated in silicotic liver.